MODEL PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAGERIA - Kurniasari, Dian (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
Performance is an important part of an organization, either a business or non business. To perform well, it is very dependent on the role of a manager. The present research seeks to investigate the effect of budget preparation participation on the managerial performance with job relevant information, job satisfaction and motivation as the intervening variables.